Analisis Gaya Kepemimpinan Kepala Sekolah dalam Novel Totto Chan: The Little Girl At The Window Karya Tetsuko Kuroyanagi - Mulki Neli Zakana; Nurul Latifatul Inayati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The role of a leader in an organization has a crucial role. The progress or decline of an organization can be influenced by the ability of a leader in leading an organization, as well as the role of the principal in leading an educational institution or school. A professional principal certainly understands how to manage school resources, is able to see all existing potentials and can optimize them, and can provide education that is tailored to the needs and developments of the times. In its implementation, to realize educational goals, cooperation and coordination are needed, not only by the principal, but also by all stakeholders, both teachers and staff, students, and also the environment (social) which in this sense is the role of parents (guardians). The method used in this study is a literature review or library research with data collection techniques using documentation in the form of primary or main data sources in the form of literary works of the novel Totto Chan: The Little Girl At The Window (in Indonesian Totto Chan: Gadis Kecil di Jendela) by Tetsuko Kuroyanagi and secondary data sources in the form of journal literature or articles and books that are relevant to the topic discussed. The purpose of this study is to determine the types of popular leadership styles that exist in schools and also to analyze more deeply the leadership styles carried out by the principal in the literary work of the novel Totto Chan: The Little Girl At The Window. The results of the data analysis that have been carried out by the researcher are, there are several popular leadership styles that exist in schools, namely: autocratic leadership style, democratic leadership style, Laissez faire leadership style, managerial leadership style, transformational leadership style and transactional leadership style, while the leadership style used by the principal in the literary work of the novel Totto Chan: The Little Girl At The Window uses a democratic-transformational leadership style. The urgency of this study is to increase the reader's knowledge in knowing the types of leadership styles and also to make the leadership style carried out by Sosaku Kobayashi (Mr. Kobayashi) as the principal in the novel Totto Chan: The Little Girl At The Window as an inspiration in leading an educational institution or school.